Influence of structural surface roughness on the strength of layered fill bodies based on PFC2D - Jinxing WANG; Zongsheng HU; Huazhe JIAO; Xiaolin YANG; Qi ZHANG; Xiaohui LIU; Ping XU; Junqiang XU; Xun CHEN (工程科学学报)
The stratified structure of underground backfill can reduce the overall physical performance, potentially causing safety issues during mining operations. To improve the bonding quality between layers, four molds with different roughness levels (R1, R2, R3, and R4) are prepared using 3D printing technology. Uniaxial compression tests and PFC2D numerical simulations are performed on layers with varying roughness. The relationship between cemented surface roughness and backfill strength is examined by analyzing variables such as cemented surface roughness, mass fraction of slurry, cement-to-sand ratio, and filling interval time. The effect of cementation surface roughness on the uniaxial compressive strength and the strength variation trend are studied to establish the correlation between the compressive strength and cemented surface roughness of the backfill. The test results reveal the following. First, when mass fraction of slurry, cement-to-sand ratio, and filling interval time kept constant, the compressive strength of the backfill increases with surface roughness. When the bonding surface roughness reaches a certain value, the compressive strength of the backfill increases with the mass fraction of slurry and cement-to-sand ratio but decreases with an increase in the filling interval. Linear and quadratic polynomial fittings of strength versus roughness reveal a quadratic polynomial relationship between strength and roughness, indicating that this function effectively characterizes the correlation between the compressive strength and bonding surface roughness of the backfill. Second, by introducing the strength enhancement coefficient (r) of the backfill, it is found that when the cement surface roughness is constant, the value of r tends to be positively correlated with the mass fraction of slurry and cement-to-sand ratio and negatively correlated with the slurry filling interval time. This indicates that increasing the mass fraction of slurry and cement-to-sand ratio can effectively enhance the positive effect of roughness on strength, whereas an increase in the filling interval time has the opposite effect. Third, when the cemented surface is rough and horizontal, the damage to the backfill is mainly concentrated along the stratified surface, and it appears in the form of penetrating tension and upper crushing failures in the vertical direction. The backfill at the lower part of the stratified plane remains mostly intact. As the cemented surface roughness increases, the failure gradually becomes more uniform across the backfill specimens, mainly in the form of overall penetrating tension failure. Discrete element simulations using PFC2D demonstrate that the internal microscopic crack evolution and distribution in the four numerical models with different cemented surface roughness agree with the failure morphology of the backfill observed in laboratory tests. The cracks form as large macroscopic fractures in the vertical direction, indicating that as the interface roughness increases, the quality of the bonding surface improves, leading to more efficient usage of the overall mechanical properties of the specimens. The findings of this study provide a theoretical and scientific basis for mine slicing and filling.